The Semiotics Of Writing: The Novels By Dževad Karahasan - Hadžizukić, Dijana (Slavica Lodziensia, 2017)
This paper will analyze Dzevad Karahasan’s novels The Eastern Diwan,Shahriar’s Ring and What the Ashes Tell, and it will do so by exploring thematisation and frames, authorship and manuscripts. In that context it is important to analyze the structural position of the authorwithin the text of the novel,his position inside the fi ctional society built within the plot, and to explore the themes and motifs of texts, scripts, writings and their overall importance, but also the meaning of the text to its fi nal recipient, the reader. The notion of writing is here considered in the sense of the Barthean term of scribing, and not only by hand, but by any other form of writing, copying, authorship and rewriting. The protagonists of Karahasan’s novels act as people who write, so the sole act of writing is made into a fundamental motif of the novel.